Tanggung Jawab Dokter Terhadap Pasien Dalam Operasi Bedah Caesar di RSUD Dr. Moewardi Surakarta - Primatama, Edward, Nuswardhani, S.H., S.U, Darsono, S.H., M.H (2016)
The purpose of this research is to describe the agreement executed between doctors and patients in the cesarean, to describe the rights and obligations of each party to the agreement to the cesarean, to describe the legal responsibility of the doctor in the event of an error in the implementation of the cesarean. This research uses normative approach and using a qualitative approach. Descriptive research. Data analysis methods used by the author is a qualitative approach. In the doctor's responsibility to patients in Caesarian section at the Hospital Dr. Moewardi is Associated with the hospital accountable for errors / omissions performed on patients, then dr. Robert Ridun gives an example of a patient who came to the hospital to give birth to the baby, and then based on the results of inspection and previous actions, the patient can not give birth the normal way. Based on the stages of childbirth patient, then the patient has to go through the stages of induction (grandstand). The doctor explained the various information about the induction action, including the risks faced by such action. It has agreed to undertake an induction by both parties by signing the informed consent. At the time of induction, the doctor all that he can to help these patients, due to negligence of doctors then an accident occurs and a hands-born babies have cracks.